If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + -2) = 5(x + 2) Reorder the terms: 3(-2 + x) = 5(x + 2) (-2 * 3 + x * 3) = 5(x + 2) (-6 + 3x) = 5(x + 2) Reorder the terms: -6 + 3x = 5(2 + x) -6 + 3x = (2 * 5 + x * 5) -6 + 3x = (10 + 5x) Solving -6 + 3x = 10 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -6 + 3x + -5x = 10 + 5x + -5x Combine like terms: 3x + -5x = -2x -6 + -2x = 10 + 5x + -5x Combine like terms: 5x + -5x = 0 -6 + -2x = 10 + 0 -6 + -2x = 10 Add '6' to each side of the equation. -6 + 6 + -2x = 10 + 6 Combine like terms: -6 + 6 = 0 0 + -2x = 10 + 6 -2x = 10 + 6 Combine like terms: 10 + 6 = 16 -2x = 16 Divide each side by '-2'. x = -8 Simplifying x = -8
| x+19+2x=-5-2x-11 | | 13x=130-x | | 2(x-5)=3(x+2) | | 6c^2-48c+90=0 | | 2n+48=-6n | | 7(x-3)=8(x+1) | | -5(-1-2k)=85 | | -15x-20=-12x+100 | | 5(x-2)=6(x+1) | | 4(x-5)=5(x+2) | | 5(12-3w)+25w=2w | | c^2+6c+5=0 | | 272=-8(-4+6a) | | -15x-20=-2x+100 | | 252=-4(7x-7) | | 3(x-2)=4(x+1) | | 18-5x=12+x | | 5(12-3w)+25=2w | | 4r=48 | | 243=27r | | 3x-9=4x | | 5(12-3)+25=2w | | 5x-8=7x | | -2+6n=-80 | | 4x=2x+19 | | ag-14=2g | | 5(x+2)+8=28 | | 49x^2=28x-4 | | 6x^2-15x+14x-35=0 | | 2(x+5)+7=19 | | 5x+4=3x+2 | | -2+6n=-8 |